Global distribution, traditional and modern detection, diagnostic, and management approaches of Rhizoctonia solani associated with legume crops - Akber, Muhammad Abdullah; Mubeen, Mustansar; Sohail, Muhammad Aamir; Khan, Sher Wali; Solanki, Manoj Kumar; Khalid, Rida; Abbas, Aqleem; Divvela, Praveen Kumar; Zhou, Lei (Frontiers in Microbiology, 2023)
Sustainable development relies heavily on a food system that is both safe and secure. Several approaches may lead to sustainability and food safety. An increase in the cultivation of legume crops is one of the approaches for enhancing agricultural viability and ensuring adequate food supply. Legumes may increase daily intake of fiber, folate, and protein as substitutes for meat and dairy. They are also crucial in various intercropping systems worldwide. However, legume production has been hampered by Rhizoctonia solani due to its destructive lifestyle. R. solani causes blights, damping off, and rotting diseases in legume crops. Our knowledge of the global distribution of R. solani associated with legume crops (alfalfa, soybean, chickpea, pea, lentil, common bean, and peanut), detection, diagnosis, and management of legume crops diseases caused by R. solani is limited. Traditional approaches rely on the incubation of R. solani, visual examination of symptoms on host legume crops, and microscopy identification. However, these approaches are time-consuming, require technical expertise, fail to detect a minimal amount of inoculum, and are unreliable. Biochemical and molecular-based approaches have been used with great success recently because of their excellent sensitivity and specificity. Along with conventional PCR, nested PCR, multiplex PCR, real-time PCR, magnetic-capture hybridization PCR, and loop-mediated isothermal amplification have been widely used to detect and diagnose R. solani. In the future, Next-generation sequencing will likely be used to a greater extent to detect R. solani. This review outlines global distribution, survival, infection and disease cycle, traditional, biochemical, molecular, and next-generation sequencing detection and diagnostic approaches, and an overview of the resistant resources and other management strategies to cope with R. solani.